The professional and socio-cultural activities of public elementary school teachers in the Division of Bataan - Legaspi, Felisa R. 1930- (s.n.], 1970)
The purpose of the study is to determine the professional and socio-cultural activities of public elementary school teachers and its implications on the division of Bataan. Findings of the study may help the school officials in planning a well-rounded professional and socio-cultural calendar of activities for teachers.